Profesionalitas Guru SMA dalam Pembelajaran Pendidikan Agama Kristen pada Masa Pandemi Covid-19 - Febilia Melanie Kasiuhe; Julius H. Lolombulan (Jurnal Ilmiah Wahana Pendidikan, 2021)
The objectives of this study are: 1) to describe and analyze the professionalism of high school teachers in learning Christian Religious Education during the Covid-19 pandemic, 2) to describe and analyze the inhibiting and supporting factors for learning Christian Religious Education during the Covid-19 pandemic, and 3) to describe and analyze the efforts made by teachers in overcoming the problem of learning Christian Religious Education during the Covid-19 pandemic. In this study, the researcher used a qualitative approach with a case study method. In this study, the researcher became the main instrument and the Christian Religious Education teacher became the main informant. This research was conducted at SMA Negeri 1 Siau Timur. The findings in this study are that during the Covid-19 pandemic like this, Christian Religious Education teachers have carried out their responsibilities well. However, it is not yet fully professional. This is caused by several factors: the lack of use of learning media, teachers are still focused on the use of the lecture method, and Christian Religious Education teachers are still not fully able to increase student participation or activeness in learning. The supporting factors for learning Christian Religious Education at SMA Negeri 1 Siau Timur include: parental support, the existence of associations that participate in shaping the personality of students, the enthusiasm of students, networks and internet quotas. While the inhibiting factors include: unstable electricity which affects internet connections, lack of internet quota, and the presence of some students who are less enthusiastic and do not receive support from their parents. Regarding the efforts made by the teacher to overcome learning problems, among others: taking steps to call or visit, provide motivation for students to keep the spirit, then pray diligently, worship diligently, read the word diligently, take care of health, obey health protocols, and ask students to read the material shared and then make a summary.